Sweden's Constitution Decides Its Covid-19 Exceptionalism - Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2020)
The Swedish policy response to covid-19 stands out as exceptional in international comparisons. The approach adopted is fundamentally determined by the Swedish constitution. Three articles of the constitution are central for this explanation. The first one guarantees the freedom of movement for Swedish citizens, thus ruling out the use of nation-wide lockdowns as an instrument in peacetime. The second one establishes independence for public agencies, allowing them to design and administer the policy response to the pandemic with a minimal interference by the central government. The third one reserves exceptional powers to local government, making a central response to the pandemic difficult to implement. In addition, the Swedish approach is fostered by strong trust by the public in the government, in public authorities and in the workings of the political system.
Keywords: E65; E71; F52; H10; H40; H70; I10; 330; Sweden; covid-19; pandemic; constitution; trust.